Generation Z's Perception of Gibran's Candidacy as Vice President in the 2024 Election in Medan City - Ridwan Nasution; Hidayat, Fadhil Pahlevi; Nasywa Fathya Rosa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Gibran's candidacy as Vice President in the 2024 election is a new phenomenon in Indonesian politics. The reason is, that Gibran was chosen by Prabowo as his running mate in the election contestation at a young age. This reaps diverse perceptions, including Generation Z where researchers conduct research. The purpose of this study is to determine Generation Z's perception of Gibran's candidacy as Vice President in the 2024 election. In this study, researchers used qualitative research methods with a phenomenological approach. Based on the results, the perception of Generation Z towards Gibran's nomination as Vice Presidential Candidate in the 2024 election has positive and negative perceptions that arise based on three things, namely sensation, attention, and interpretation by each Generation Z. Positive perceptions are formed because the information obtained by generation Z is related to Gibran's track record of ability in handling the City of Solo, as a form of proof that young people are capable of becoming leaders, and as a novelty in the world of Indonesian politics. Negative perceptions are present because the information received by Generation Z related to Gibran's nomination at a young age cannot be separated from the efforts of the Constitutional Court as Gibran's uncle passed Gibran's age, and Gibran's nomination was likely planned